A review of the potential health benefits of pine nut oil and its characteristic fatty acid pinolenic acid - Kayin Xie; Elizabeth A. Miles; Philip C. Calder (Journal of Functional Foods, 2016)
Pine nuts contain pinolenic acid (PNLA), which represents 14–19% of fatty acids present. Here we review research on pine nut oil (PNO) and PNLA from studies performed in vitro, in animal models and in humans. PNLA has anti-inflammatory action and may improve lymphocyte function. PNO and PNLA have favourable effects on appetite control, perhaps by increasing the blood concentrations of key satiety hormones. Less weight gain and fat deposition were observed in mice fed with high fat diets containing PNO. In vitro research demonstrated that PNLA is a potent dual agonist for co-activation of free fatty acid receptors 1 and 4, which could enhance glucose-dependent insulin secretion and insulin sensitivity. PNO increased the activity of antioxidant protective enzymes in serum and decreased the concentration of malondialdehyde, an indicator of lipid peroxidation. Thus, PNLA and its parent PNO could be of potential benefit to human health, although this requires further investigation.